Programa de Aquisiç\~ao de Sementes e Mudas Nativas (Pasem): Uma proposta de política pública para fins de regularizaç\~ao ambiental no Brasil - Jo\~ao Daldegan; Regina Helena Rosa Sambuichi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– In accordance with the Brazilian Forest Legislation, nearly 12.5 million hectares of native vegetation must be restored over the next 20 years in the country. The feasibility of this process will depend on the existence of a supply of seeds and native seedlings with adequate quality, diversity and quantity to be planted in these areas. This text aims to present a public policy proposal to promote the production of seeds and native forest seedlings to support Brazil's environmental regulation. A historical analysis of the country's forest policy shows that there have been few official incentives for structuring the chain of forest restoration, unlike the reforestation with exotic species. Among the main challenges encountered in the production growth of seeds and native seedlings are the lack of a continuous demand and the bureaucratic obstacles to its commercialization. To overcome such challenges it was proposed the creation of a public policy of government procurement, to which it was suggested the name Seeds and Native Seedlings Acquisition Program. The elements of the proposal were based on the example set by the Foods Acquisition Program and on the experience of the networks of Brazilian seeds. The proposed program will allow the purchase of seeds and native forest seedlings directly from family farmers without bidding, which gives it a social and environmental character. Besides supporting the environmental regulation, it will generate employment and income for family farmers.
Keywords: Q23; Q28; 330; public policy; native forest seeds; forest restoration; Forest Code; National Institute of Colonization and Agrarian Reform (Incra)